Protein network formation during pound cake baking: The role of egg yolk and its fractions. (February 2017) - Deleu, Lomme J.; Melis, Sara; Wilderjans, Edith; Van Haesendonck, Ingrid; Brijs, Kristof; Delcour, Jan A.
Abstract: Pound cake is made from equal portions of egg, wheat flour, sugar and margarine or butter. Its quality is codetermined by the protein network formed during baking. A key insight on egg yolk functionality is that during batter mixing the yolk granules disintegrate and dissolve most of their protein into the batter liquor. This was demonstrated by comparing the protein population of a reference batter liquor with that in batter liquor of which the added yolk was pretreated to disintegrate the granules. Using a 15 N-labeling approach, the protein network formation was monitored during cake baking in an electrical resistance oven. Protein was extracted in different media, i.e. diluted saline, aqueous ethanol, a buffer containing sodium dodecyl sulfate and one containing dithiothreitol, and analyzed by size-exclusion HPLC. Both egg yolk plasma and granule proteins are incorporated in the protein network by disulfide crosslinking during pound cake baking. Only phosvitin, which lacks both free sulfhydryl and intermolecular disulfide bonds, does not take part in the protein network via disulfide bridge formation. Graphical abstract: Highlights: Egg yolk granules disintegrate during pound cake mixing. Egg yolk plasma and granule proteins take part in the covalent protein network. All egg and most flour proteins (except glutenins) are found in the aqueous phase. Egg yolk proteins may form SH/SS exchange reactions with other ingredients. Phosvitin is not incorporated in the covalent protein network in pound cake.